Drivers of Inclusive Development: An Empirical Investigation - Christoph Morosoli; Peter Draper; Andreas Freytag; Sebastian Schuhmann (The European Journal of Development Research, 2024)
Abstract Concerns about socially uneven progress and inequality have regained public attention (including that of many populist politicians). The purpose of this paper is to identify the economic policies as well as economic factors that facilitate inclusive development. This paper is a first attempt to empirically estimate the drivers of inclusive development. For our empirical assessments, we apply the Multidimensional Inclusiveness Index suggested by Dörffel and Schuhmann ( 2022 ) in a panel OLS regression setup with fixed effects (FE) and GMM estimations for up to 178 countries and a time frame ranging from 1980 to 2018. In FE regressions, we find robust associations with inflation as well as financial sector development in the short and long-run, trade/GDP in the long-run. The GMM results point only to inflation and trade as significant drivers in the long-run and investment in the short run. These results suggest that accessible and well-functioning financial markets paired with low rates of inflation and high trade openness take on a more critical role than government spending. Our results suggest that rudiments of the Washington consensus could still guide the promotion of inclusive development.
Additional information: C23;D63;I31;O15
Keywords: 330; Inclusive development; Globalization; Trade; Institutions; Policies